Standards. The building blocks of complexity - Juli Peretó; Manuel Porcar (Mètode Science Studies Journal: Annual Review)
Without standards, the world as we know it would not be possible. International and supra-cultural standards and norms have been a key factor in engineering, as well as in the development of industrial societies. Despite the obvious successes in electronic and mechanical design, other technological areas present difficulties for the application of standards. In the field of biotechnology and synthetic biology – which aims at studying living things from an engineering perspective – standards are desirable, but whether they can be widely adopted remains to be proved.